THE USE OF TRUE AND FALSE ESSAY GAMES TO ENHANCE STUDENTS’ WRITING ACHIEVEMENT AND CLASSROOM INTERACTION - Anhar Anhar (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2019)
This study was aimed at investigating the students’ writing performance and classroom interaction through the use of true and false essay game strategy. This study was collaborative action research consisted of two cycles. The steps were planning, action, observation, and reflection. This research involved the 19 students of class 11th grade students of SMKN 3 Pujut. The data were qualitative in nature and supported by those of quantitative. The data were obtained from the observation sheet, questionnaire, and writing test. Meanwhile, the quantitative data were obtained by conducting writing post-test at the end of the actions. The research finding showed that use “True and False Essay Games” was proved to be significant to improve the students’ writing skills and classroom interaction. The strategy of True and False Essay Games makes an enthusiasm, empowering and challenging series of activities that vary the classroom interaction and activities during the teaching-learning process. Moreover, this strategy helped the students to build a positive relationship among them. Quantitatively, the mean of the students‟ writing scores in the pre-test is 50. Meanwhile, the students’ score of the post-test was 55. The improvement was 5 in the first cycle.  In cycle 2, the students’ score of the post-test was 80.32. In the presentations between cycle 1 and cycle 2 was 30.4 It can be concluded that the True and False Essay Games was able to enhance students’ writing skill and classroom interaction viewed from organization, content, grammar, vocabulary, and mechanics.